“I hope she dies when I die”: A mother’s experience with a child of Down syndrome - Saili, Jamayah; Ibrahim, Nor Hasniah (2013)
Clearly for most people and most cultures, having a healthy and normal child is the most awaited moment in a couple’s life. Trisomy 21, the chromosomal anomaly associated with Down syndrome (DS), is a relatively common cause of learning disability across all human populations. Limited research conducted in developing countries tends to characterise life for people with intellectual disability and their families as burdensome and stigmatised. While life experiences and expectancy for people with DS varies significantly across the world, the majority of research with families who have a child with DS has been conducted in relatively affluent western countries. It has been argued that DS is as much a cultural creation as a biomedical condition, yet the research on Malay Muslim mothers’ experience is sparse in Malaysia. Drawing on in-depth qualitative interview with a Malay Muslim mother, a cultural definition of having a DS child, the researcher argues that further work is needed to consider the viewpoints on parenting a child with DS which may have specific meanings in comparisons with other context and culture. The analysis of this in-depth interview yielded that the mother’s experience were marked by uncertainty about the child’s life course expectations and decisions. Two tenets especially germane to this issue are the child’s independence and growing older without significant people in her life and who will care for her when her parents die and how does she cope? The mother’s descriptions of life with a child with DS integrated religious and cultural belief systems and personal social experiences. Listening to the voice of a mother parenting a child with DS, this article will highlight the participant’s advice to other parents which was rooted in Islamic discourse but emphasized pragmatic concerns about the impact of having an intellectual disability as family member.